Evaluación de condiciones geomecánicas y viabilidad técnica según metodología numérica d. nicholas para selección del método de explotación en veta delia, Mina Colquirrumi - Minaya Villarreal, Johann Alexander (2019)
This thesis aims to select the exploitation method for the Delia vein deposit based on the numerical methodology of Nicholas (1981). The research is divided into three stages. The first stage consists in describing the geological conditions (shape, power, dip, depth and distribution of laws) and geomechanics (resistance of the rock matrix, spacing between fractures and resistance of discontinuities) of the rock mass for mineral rock, for rock roof box and rock floor box. The second step of the investigation is to apply the numerical methodology of Nicholas (1981) and thus obtain viable alternatives of exploitation from the technical point of view. From this second step, possible alternatives of exploitation method are obtained. Finally, the third step is to evaluate criteria: economic (reserves, tonnage, ore grade, amount of production, life of the mine), technological (recovery, dilution, flexibility and speed of development) and environmental (safety, health and workforce); criteria that allow us to establish the ideal exploitation method for the site. The evaluation and compliance with the aforementioned steps allows us to obtain an adequate exploitation method for this type of deposit. Thus establishing a valid selection process where aspects such as technical, economic, technological and environmental are evaluated.